Local regulation and function of importin-β1 in hippocampal neurons during transcription-dependent plasticity - Lee, Yan Jun (Nanyang Technological University, 2021)
Activity-dependent transcription is critical for the encoding of long-term memories. Regulated nuclear entry of soluble proteins is one method to relay synaptic signals to the nucleus to couple neuronal excitation with transcription. To date, the role of importin-β1 in nuclear shuttling of proteins during activity-dependent transcription has always been inferred but not directly investigated. In this study, activity-dependent nuclear accumulation of importin-β1 from the soma and the synapto-dendritic compartments has been demonstrated. Importantly, inhibition of importin-β1 mediated nuclear import during synaptic stimulation impairs long-term plasticity. I also show evidence that importin-β1 mRNA-ribosome complex is distributed throughout the synapto-dendritic compartment and synaptic stimulation induces importin-β1 local protein synthesis. Finally, several candidate proteins that associate with importin-β1 at the synapse have been identified from which N-Myc Downstream Regulated 1 (NDRG1) is characterized as an importin-β1 interactor that undergoes activity-dependent translocation into the nucleus. Collectively, these results highlight the crucial role of importin-β1 in nuclear import of proteins during long-term plasticity.